Meningkatkan Minat dan Prestasi Belajar Materi Pewarisan Sifat Makhluk Hidup Melalui Penerapan Model STAD pada Siswa Kelas IX-D SMP Negeri 2 Pare Kabupaten Kediri - Husnaini Na (Universitas Nusantara PGRI Kediri, 2022)
The results of monitoring the learning process and the results of the questionnaire given to class IX-D students of SMP Negeri 2 Pare, Kediri Regency, showed that students' abilities were still low in science subjects. Many students experience difficulties, especially in the matter of Inheritance of Traits in Living Things. This results in low quality of teaching and learning activities and test scores. The low quality of teaching and learning activities and test scores will have an impact on low student achievement. After examining in depth the cause of the low ability of students is the teacher's habits that dominate learning activities. Teachers assume that students will not gain knowledge if they do not transfer the knowledge they have, and assume that learning that focuses on student activities (student center) is only troublesome and results in learning objectives not being achieved. This study aims to describe natural science with the application of the STAD model which can improve science learning achievement in the subject of Inheritance of Traits in Living Things. This study used a Classroom Action Research design consisting of two cycles. Research data collection was carried out from August to October 2018. Research in the form of student activities and student achievement was obtained through tests at the end of each cycle. The results showed that students' interest increased by (14%) in cycle 1, from 70% to 84% in cycle 2. In increasing learning achievement, the number of students who met KKM standards in cycle 1 was 24 students with a mastery percentage of 66%, and students who were declared to have met the KKM standard in cycle 2 were 35 students with a completeness percentage of 97%. The percentage increase is 31% from cycle 1. So it can be concluded that the application of the STAD model can improve student achievement in class IX-D SMP Negeri 2 Pare on the material Inheritance of Traits in Living Things.